Character Construction of Pancasila Student Profiles Through Activities Religion - Aisyah Deslantari Romadhonia; Moh. Zamili (Jurnal Pendidikan Islam Indonesia, 2025)
Abstract: The character profile of Pancasila students is a formulation formed by the Ministry of Education, Culture, Research and Technology to realize character and morals in accordance with Pancasila values. In this modern era, character degradation is still something that really needs to be considered, the rampant bullying and cases of violence in the world of education are the reasons for the government to continue to improve character by constructing the character profile of Pancasila students in schools through various religious activities. The purpose of this study is to reveal how religious activities are implemented, what are the limiting factors of religious activities, and how the character profile of Pancasila students is constructed through religious activities. This type of research is qualitative with a field study method. In collecting data using interview techniques, observation and documentation. The construction of the character profile of Pancasila students through the habituation of religious activities at SMPN 4 Situbondo every day, such as kissing the teacher's hand at the school gate, followed by congregational Duha prayer, reading juz 30 before learning begins, and reading Asmaul Husna and prayers before going home, in addition there are also extracurricular BTQ and Friday worship every Friday. The implications of this study: become development material in constructing the character profile of Pancasila through the habituation of religious activities internally at SMPN 4 Situbondo. Externally, it becomes reference material in further scientific papers. Keywords: Religious Activities, Character Education, Pancasila Student Profile